SCHOOLOGY AS A LEARNING MEDIA PLATFORM FOR WRITING SKILL - Agustin Apriliani; Abdul Asib; Ngadiso Ngadiso (Universitas Muhammadiyah Semarang, 2019)
Teacher needs to give various methods to teach writing in order to increase the students’ writing achievement. To help the students write better, teacher should be able to be more creative and innovative in teaching writing. In 4.0 era, the students prefer using modern technologies (online media). Modern technologies can help the teacher and students access the lesson material, update the information that relevant with the lesson, communicate each other, or watch the teacher’s videos like on YouTube about the materials easily. There are many digital technologies such as; Blog, Website, and others. Those media can be used as learning media to support students’ writing skill, one of them is Schoology. Schoology is micro blog educational website that can be applied by teacher and students for collaborating about resources, assessment, and content on a secure and safe learning management platform. Students can post their writing task in Schoology group that created by the teacher. Then, the teacher can evaluate the students’ writing and give some suggestion or comments. In other words, Schoology give stimulation for students to try their ability in writing achievement and increase the students’ interest. This literature study reviews several papers studying the implication of Schoology as a learning media platform. The purpose of the study is to find out the implication using Schoology to the teachers and students. The findings expected that Schoology can be an alternative learning media platform that used by the teacher and the students to support teaching and learning process in writing.